Revisiting the Ukraine crisis: Realist reflections on causes and consequences - Vasif Huseynov (CES Working Papers, 2017)
This paper presents a realist reflection on the crisis in Ukraine from the perspective of the Western powers, in particular, that of the United States. Its theoretical argumentation is built on the basis of thoughts of contemporary realist minded scholars and geopoliticians, but, concomitantly, criticizes the contradictory nuances in their approaches. The paper analyses the consequences of the Ukraine crisis as an accomplishment from the Western point of view and diverges from other realist scholars who consider it as a mistake of the West. It argues that the United States has successfully completed its geopolitical mission concerning Ukraine by breaking it away from Moscow's sphere of influence, therefore, now it can seek to de-escalate tensions with Russia over Ukraine and re-direct its focus on other threats, such as the rise of China.
Keywords: 330; Geopolitical Realism; the Ukraine Crisis; EU; United States; Russia